Law and Language in the Middle Ages - Benham, Jenny; McHaffie, Matthew; Vogt, Helle (Medieval Law and Its Practice, 2018)
Law and Language in the Middle Ages investigates the relationship between law and legal practice from the linguistic perspective, exploring not only how legal language expresses and advances power relations but also how the language of law legitimates power.; Readership: With its disciplinary approach, and chronological and geographical range, this volume will be of interest to scholars and students of law, history, medieval languages, translation studies and digital humanities.